Strategi Komunikasi Perpustakaan dalam Meningkatkan Daya Tarik Pengunjung Perpustakaan Pasca Pademi - Sinta Azhary Ginting; Dewi Kurniawati (Peneliti.net, 2023)
Libraries in increasing their usefulness after the pandemic need to update the methods used to attract users' attention. Changes were made either through regulatory changes, adding programs and services or improving communication strategies with users. One of the tools for communication is social media. Including the USU library using social media in increasing the attractiveness of service utilization by users. However, on the other hand, there has been a change in the communication strategy adopted by the library in the post-pandemic period. From this, the author is interested in studying USU's library communication strategy in increasing the attractiveness of users to visit the library and take advantage of library services in the post-pandemic period. This study asks about the form of communication strategies used by the USU library in reaching out to users. Given that there has been a change in student communication patterns in obtaining information before the pandemic and post-pandemic. Library marketing is one of the keys to the sustainability and use of the library by users. One of the tools used by libraries to disseminate their activities and information is social media.